Comparison of Hematology Analyzer Cyanmethemoglobin Method and Point-of-Care Testing (POCT) Electrode-Based Biosensor Method in Measurement of Hemoglobin - LISANA SHIDQI; RATNA KUSUMAWATI; RATIH DEWI YUDHANI (Nexus Biomedika, 2017)
Introduction: Measurement of hemoglobin concentration can be done by hematology analyzer (HA) cyanmethemoglobin method (gold standard) and point-of-care testing (POCT) electrode-based biosensor method. POCT electrode-based biosensor method is one of the hemoglobin POCT and has not been studied before in Indonesia. This study examined the difference and correlation hemoglobin concentration by HA cyanmethemoglobin method and POCT electrode-based biosensor method. Methods: This was a cross sectional study in 4 senior high schools of Sukoharjo in Indonesia on Desember, 2016. Senior high schools were selected using a simple random sampling and senior high schools grade selected using a stratified random sampling. Among 173 grade 10 and 11 senior high school girls in this study the capillary and venous blood samples were collected. Capillary blood sample collected was immediately processed to measure the hemoglobin concentration using POCT electrode-based biosensor method and venous blood sample was collected to measure the hemoglobin concentration using HA cyanmethemoglobin method. Statistical analyses used were Mann-Whitney and Spearmans correlation coefficient (?=0.05). Results: Hemoglobin concentration determined by the POCT electrode-based biosensor method compared to HA cyanmethemoglobin method was significantly different (p=0.000 ) and there was positive moderate correlation (r=0.438; p=0.000). Conclusions: Hemoglobin concentration assessment by POCT electrode-based biosensor method has shown significantly different and positive correlation with HA cyanmethemoglobin method. Keywords: hemoglobin concentration, HA cyanmethemoglobin method, POCT electrode-based biosensor method